Localization and functional analysis of the insect‐specific RabX4 in the brain of Bombyx mori. Issue 1 (14th July 2017) - Uno, Tomohide; Furutani, Masayuki; Sakamoto, Katsuhiko; Uno, Yuichi; Kanamaru, Kengo; Mizoguchi, Akira; Hiragaki, Susumu; Takeda, Makio
Abstract: Rab proteins are small monomeric GTPases/GTP‐binding proteins, which form the largest branch of the Ras superfamily. The different Rab GTPases are localized to the cytosolic face of specific intracellular membranes, where they function as regulators of distinct steps in membrane trafficking. RabX4 is an insect‐specific Rab protein that has no close homolog in vertebrates. There is little information about insect‐specific Rab proteins. RabX4 was expressed in Escherichia coli and subsequently purified. Antibodies against Bombyx mori RabX4 were produced in rabbits for western immunoblotting and immunohistochemistry. Western blotting of neural tissues revealed a single band, at approximately 26 kD. RabX4‐like immunohistochemical reactivity was restricted to neurons of the pars intercerebralis and dorsolateral protocerebrum in the brain. Further immunohistochemical analysis revealed that RabX4 colocalized with Rab6 and bombyxin in the corpus allatum, a neuronal organ that secretes neuropeptides synthesized in the brain into the hemolymph. RabX4 expression in the frontal ganglion, part of the insect stomatogastric nervous system that is found in most insect orders, was restricted to two neurons on the outer region and did not colocalize with allatotropin or Rab6. Furthermore, RNA interference of RabX4 decreased bombyxin expression levels in the brain. These findings suggest that RabX4 is involved in the neurosecretion of a secretory organ in Bombyx mori .